1996
DOI: 10.1017/s0954579400007240
|View full text |Cite
|
Sign up to set email alerts
|

Attachment and teacher-reported behavior problems during the preschool and early school-age period

Abstract: The association between attachment and behavior problems was examined for a nonclinical, diverse sociocconomic status (SES) French-Canadian sample of 77 children. Attachment classifications were assigned on the basis of reunion behavior with mother when the children were between 5 and 7 years of age. Teachers rated children's problem behavior using the Socioaffective Profile within 3 months of the attachment assessment (Time 2) and 2 years earlier (Time 1). Results indicated that children with a D classificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
69
0
20

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(98 citation statements)
references
References 43 publications
9
69
0
20
Order By: Relevance
“…El hecho de que entre los participantes que no habían ejercido violencia no existiera el apego temeroso -coincidente con el apego desorganizado de Main y Solomon (1990)-fortalece las teorías que explican que el apego desorganizado se relaciona cercanamente con el ejercicio de la violencia por parte de los hombres (Lyons-Ruth et al, 1993Main & Solomon, 1990;Moss et al, 1996). Este hallazgo podría explicar algunas conductas presentes en los hombres que han ejercido violencia hacia sus parejas, que se relaciona, entre otros aspectos, con la necesidad imperiosa de controlar al otro (Lyon-Ruth et al, 1993).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…El hecho de que entre los participantes que no habían ejercido violencia no existiera el apego temeroso -coincidente con el apego desorganizado de Main y Solomon (1990)-fortalece las teorías que explican que el apego desorganizado se relaciona cercanamente con el ejercicio de la violencia por parte de los hombres (Lyons-Ruth et al, 1993Main & Solomon, 1990;Moss et al, 1996). Este hallazgo podría explicar algunas conductas presentes en los hombres que han ejercido violencia hacia sus parejas, que se relaciona, entre otros aspectos, con la necesidad imperiosa de controlar al otro (Lyon-Ruth et al, 1993).…”
Section: Discussionunclassified
“…La violencia en general ha sido mayoritariamente relacionada con el apego desorganizado (Lyons-Ruth, et al, 1993Main & Solomon, 1990;Moss, Parent, Gosselin, Rousseau & St-Laurent, 1996), caracterizado por una actuación parental estresante e incoherente para el niño, como maltrato infantil, abuso, negligencias o la presencia de patologías en los cuidadores. Estas dinámicas propician la generación de modelos mentales en conflicto, puesto que la figura de apego es fuente de protección y de amenaza a la vez (Main & Solomon, 1990), y conllevarían al desarrollo de ciertas dificultades importantes en la adultez, como sentido inestable del sí mismo, irritabilidad, inestabilidad emocional e impulsividad, entre otras (Fonagy et al, 2000).…”
Section: Apego Y Violenciaunclassified
“…Behavioral (Crittenden 1992;Main and Cassidy 1988;Moss et al 1996Moss et al , 1998 and representational (Main et al 2005) measures of attachment extend only until early middle childhood.…”
Section: Introductionmentioning
confidence: 99%
“…A separate review by Van IJzendoorn and Bakermans-Kranenburg, 23 using a meta-analysis, found an overall effect size of r = 0.29 across 12 studies for an association between disorganised attachment and childhood behaviour problems. 24,31,45,[163][164][165][166][167][168][169][170][171] As Green and Goldwyn 147 pointed out, the high base rates of attachment insecurity in the general population of up to 40% have made it difficult to use this as a predictor of psychopathology. Although disorganised attachment is less common and has associations with future psychopathology and other problems, it also encompasses a heterogeneous group in terms of the behaviours displayed in the SSP.…”
Section: Resultsmentioning
confidence: 99%